Combined iStent® Inject Trabecular Micro-Bypass and Phacoemulsification in Australian Patients with Open-Angle Glaucoma - Salby AM (Dove Medical Press, 2020)
Alon M Salby,1 Simon E Skalicky1,2 1Department of Ophthalmology, Royal Melbourne Hospital, Melbourne, VIC, Australia; 2Glaucoma Unit, Royal Victorian Eye and Ear Hospital, Melbourne, VIC, AustraliaCorrespondence: Alon M Salby Email amicahmd@gmail.comPurpose: This retrospective audit aimed to evaluate the impact of combined iStent® Inject (iSI) and phacoemulsification on medication number in Australians with open-angle glaucoma. Secondary outcomes included intraocular pressure (IOP), best-corrected visual acuity, refraction and visual fields.Patients and Methods: Patients with glaucoma that received combined iSI and phacoemulsification by the same surgeon between 1 February 2016 and 1 February 2018 were audited for postoperative medication number, pressures after 1 day, 1 week, 4 weeks and 6, 12, 18 and 24 months, visual acuity, refraction and visual fields. These parameters were compared to baseline levels and with those from a separate cohort of patients without glaucoma that received standalone phacoemulsification.Results: Forty-one patients (63 eyes) received the combined procedure. Thirty-four patients (59 eyes) received standalone phacoemulsification. Four weeks after receiving combined iSI and phacoemulsification the mean medication number was significantly reduced by 1.3 (p < 0.001) for those on medication at baseline and by 0.5 (p = 0.002) overall. Mean IOP was significantly reduced from baseline after 6 months (– 16%; p = 0.012; n = 35) and 12 months (– 29%; p = 0.004; n = 16). Patients receiving standalone phacoemulsification had short-term reductions in IOP at 4 weeks (– 8%; p < 0.001; n = 57) and 6 months (– 16%; p < 0.001; n = 32). These patients without glaucoma had lower pressures overall compared to those with glaucoma that received the combined procedure (p = 0.019). There were no differences in final visual acuity or refractive outcomes between groups.Conclusion: This audit suggests that iSI and phacoemulsification are at least as effective in controlling IOP as medical therapy. It may have an important role in reducing the medication burden in Australians with cataract and glaucoma. This study is one of the first to confirm refractive stability in concomitant iSI and phacoemulsification.Keywords: glaucoma, iStent Inject, micro-invasive glaucoma surgery, trabecular micro-bypass, phacoemulsification